Sis peces teatrals reaparegudes del teatre valencià. - SALES BAVIERA, JOANA (Scripta, 2021)
During the period of the 19th century, the Valencian theater represented by the genre of one act play, called by many scholars a work of laughter, had a very marked repercussion. But not the cult theater, which due to circumstances, among which was the lack of linguistic, orthographic and grammatical regulations, did not become one of the priorities of the Valencian xix century writers. Then, we find how the one act play written with its colloquial register, is the literary genre that represents the so-called Valencian theater of the time. Thanks to legacies and collections, researchers have been classifying and compiling these works that are part of our literature. In this study we will present six plays corresponding to the aforementioned century. We have been able to extract these pieces, which have disappeared, thanks to the legacy of one of the most important theaters in the city of Valencia, the Theater Russafa.